Shape memory alloy actuation effect on subsonic static aeroelastic deformation of composite cantilever plate - Hussein, A. M. H.; Abang Abdul Majid, Dayang Laila; Abdullah, Ermira Junita (Institute of Physics Publishing, 2016)
Shape memory alloy (SMA) is one of the smart materials that have unique properties and used recently in several aerospace applications. SMAs are metallic alloys that can recover permanent strains when they are heated above a certain temperature. In this study, the effects of SMA actuation on the composite plate under subsonic aeroelastic conditions are examined. The wind tunnel test is carried out for two configurations of a cantilever shape memory alloy composite plate with a single SMA wire fixed eccentrically. Strain gage data for both bending and torsional strain are recorded and demonstrated during the aeroelastic test for active and non-active SMA wire in two locations. The cyclic actuation of the SMA wire embedded inside the composite plate is also investigated during the aeroelastic test. The results show reduction in both bending and torsional strain of the composite plate after activation of the SMA wire during the wind tunnel test.